Magnolia quetzal and Magnolia mayae, a new species and a new record, respectively, for the flora of Guatemala - Vázquez-García, J. Antonio; Véliz-Pérez, Mario Esteban; Tribouillier-Navas, Erick; Muñiz-Castro, Miguel A. (Phytotaxa, 2013)
Magnolia quetzal, a new species from Quiché, Guatemala is described and illustrated; it belongs to section Talauma, subsection Talauma; it differs from M. morii in having much larger flowers, thinner leaf blades, usually longer petioles larger fruits and larger number of carpels and stamens. Magnolia mayae from Huehuetenango is here presented as the first record for the Flora of Guatemala.